Incidencia de la encefalopatía hipóxico-isquémica e implementación de la hipotermia terapéutica por regiones en España - Juan Arnaez; Alfredo García-Alix; Gemma Arca; Eva Valverde; Sonia Caserío; M. Teresa Moral; Isabel Benavente-Fernández; Simón Lubián-López (Elsevier, 2018)
Resumen: Introducción: La incidencia de la encefalopatía hipóxico-isquémica perinatal (EHI) y la implementación de la hipotermia terapéutica (HT) es desconocida en España. Método: Estudio transversal nacional en recién nacidos vivos (RNV) ≥ 35 semanas de gestación mediante cuestionario on-line en las 90 unidades neonatales de nivel iii. Se solicitaron datos de los RNV con EHI moderada-grave en los años 2012 y 2013, y de la implementación de la HT en junio del 2015. Resultados: Se recibieron datos de los 90 hospitales. La incidencia de EHI moderada-grave fue 0,77/1.000 RNV (IC del 95%, 0,72; 0,83). El 86% de los RNV con EHI recibieron HT (activa o pasiva), aumentando los que recibieron HT activa del 78% en 2012 al 85% en 2013 (p = 0,01). El 14% no recibió HT principalmente por retraso en el diagnóstico o en el traslado, o por no indicarse el tratamiento. El 57% de los RN nació en hospitales sin HT, siendo el traslado en hipotermia pasiva; en el 39% por equipos sin formación adecuada. En junio del 2015, 57/90 centros realizaban HT: 54 HT corporal total activa (todos con dispositivos servocontrolados). Existió heterogeneidad en la distribución por comunidades autónomas (CC. AA.) de centros con HT activa y en el número de RN que recibieron HT. Conclusiones: La incidencia de EHI moderada-grave es homogénea entre CC. AA. Aunque se constata un importante progreso en la implementación de la HT, es preciso mejorar la disponibilidad de HT activa entre CC. AA., así como el diagnóstico precoz y el traslado con garantías desde los centros emisores. Abstract: Introduction: There are no data on the incidence of hypoxic-ischaemic encephalopathy (HIE) and the implementation of therapeutic hypothermia (TH) in Spain. Methods: This is a cross-sectional, national study, performed using an on-line questionnaire targeting level III neonatal care units in Spain. Participants were requested to provide data of all newborns ≥ 35 weeks of gestational age diagnosed with moderate-severe HIE over a two year-period (2012-2013), and of the implementation of TH up to June 2015. Results: All (90) contacted hospitals participated. HIE incidence rate was 0.77/1000 live newborns (95% CI 0.72 - 0.83). During 2012-2013, 86% of the newborns diagnosed with moderate-severe HIE received TH (active or passive). Active TH was increasingly used, from 78% in 2012 to 85% in 2013 (P=.01). Of the 14% that did not receive TH, it was mainly due to a delay in the diagnosis or inter-hospital transfer, and to the fact that the treatment was not offered. More than half (57%) were born in hospitals where TH was not provided, and passive hypothermia was used for inter-hospital patient transfer, and in 39% of the cases by inappropriately trained personnel. By June 2015, 57 out of 90 centres had implemented TH, of which 54 performed whole-body TH (using servo-controlled devices). The geographical distribution of centres with active TH, and the number of newborn that received TH, was heterogeneous. Conclusions: The incidence of moderate-severe HIE is homogeneous across Spanish territory. Significant progress is being made in the implementation of TH, however it is necessary to increase the availability of active TH between Autonomous Communities, to improve early diagnosis, and to guarantee high quality patient transfer to referral centres.